Colistin-Resistant mcr-1-Positive Escherichia coli ST131-H22 Carrying blaCTX–M–15 and qnrB19 in Agricultural Soil - Lopes, Ralf; Furlan, João Pedro Rueda; dos Santos, Lucas David Rodrigues; Gallo, Inara Fernanda Lage; Stehling, Eliana Guedes (Frontiers in Microbiology, 2021)
The pandemic Escherichia coli sequence type 131 (ST131) carrying plasmid-mediated colistin resistance mcr genes has emerged worldwide causing extraintestinal infections, with lineages belonging to three major clades (A, B, and C). Clade B is the most prevalent in animals, contaminating associated meat products, and can be transmitted zoonotically. However, the blaCTX–M–15 gene has only been associated with C2 subclade so far. In this study, we performed a genomic investigation of an E. coli (strain S802) isolated from a kale crop in Brazil, which exhibited a multidrug-resistant (MDR) profile to clinically significant antimicrobials (i.e., polymyxin, broad-spectrum cephalosporins, aminoglycosides, and fluoroquinolones). Whole-genome sequencing analysis revealed that the S802 strain belonged to serotype O25:H4, ST131/CC131, phylogenetic group B2, and virotype D5. Furthermore, S802 carried the clade B-associated fimH22 allele, genes encoding resistance to clinically important antimicrobials, metals, and biocides, and was phylogenetically related to human, avian, and swine ST131-H22 strains. Additionally, IncHI2-IncQ1, IncF [F2:A-:B1], and ColE1-like plasmids were identified harboring mcr-1.1, blaCTX–M–15, and qnrB19, respectively. The emergence of the E. coli ST131-H22 sublineage carrying mcr-1.1, blaCTX–M–15, and qnrB19 in agricultural soil represents a threat to food and environmental safety. Therefore, a One Health approach to genomic surveillance studies is required to effectively detect and limit the spread of antimicrobial-resistant bacteria and their resistance genes.